SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MAKALAH SEMINAR TERBAIK (Studi Kasus : Seminar Riset Teknologi dan Informasi STMIK AKAKOM) - , Deborah Kurniawati, S.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The selection of the best conference papers is an appreciation that can be provided by the organizers of the seminar to the authors of papers. In addition to a number of papers, differences in style and judgment of the reviewer, the diversity and complexity of the various sciences